Moving toward the Museum in 18th-Century Germany - Schellenberg, Renata (Material Culture Review, 2012)
In the 18th century, the museum experience in Germany was largely a theoretical enterprise. Despite efforts to initiate the museum as a civic institution, the majority of collections in Germanophone Europe remained in private ownership until much later in the century, secluded from public view and difficult to access in conventional terms. Visitation to collections was consequently limited to the initiated (and invited) few, who often travelled great distances to view displayed objects and who then communicated their knowledge of exhibits to others in a series of aesthetic writings. This article examines the intense interaction of print culture and collecting practices in 18th-century Germany by focusing specifically on the vital interconnection existing between discursivity and the physical object. It explores the general nature of this relationship, while also illustrating the impact it had on the nascent public practice of collecting in Germany. It regards the promulgation of collecting within this context primarily as a textual strategy, rather than as a factual reality, and evaluates the role reading played in promoting the acquisition and collection of material culture to a post-Enlightenment general public.